Paulo Freire's Philosophy of Education in the Review of Islamic Education - Efi Afifi (Civiliza Publishing, Indonesia., 2026)
Liberating Educationas a concept in Paulo Freire's Philosophy of Education emphasizes the process of conscientization, which refers to the process of humanizing human beings. Education must involve critical awareness as an implication of the dialogical process that serves as its spirit. Thus, dialogue becomes a tool for liberation and positions human beings equally as subjects of change. This paper examines how this concept, which originates from Western epistemology, is viewed from the perspective of Islamic educational studies, so that Paulo Freire's concept does not lose its spiritual meaning. In Islam, education has three dimensions: first, the divine dimension (ilahiyah), which explains the relationship between individuals and their God; second, the human dimension (insaniyah), which explains the relationship between individuals and other human beings; and third, the natural dimension ('alamiyah), which explains the relationship between individuals and the universe.